The efforts for cork oak forest management and their effects on soil conservation - Laouina, A.; Aderghal, M.; Al Karkouri, J.; Antari, M.; Chaker, M.; Laghazi, Y.; Machmachi, I.; Machouri, N.; Nafaa, R.; Naïmi, K.; Nouira, A.; Sfa, M. (Forest Systems, 2010)
The Shoul oak grove is a forested ecosystem inherited from a Holocene phase of ecological optimum; its evolution, through the double geologic and human temporality, and in relation with several processes of degradation, led to the progressive loss of its environmental equilibrium and further to the reduction of its economic contributions. The fragility of these forests is the consequence of the convergence of two main factors, i) the intrinsic fragility of the forested environment based on an unstable balance between the tree, the leached soils and their moisture content ; ii) the anthropological action on the forest environment and its degradation with the change of its floristic composition. During the colonization the new context was at the origin of the new social and economic relation between the forest and the surrounding populations. The current use of this oak grove is in a classic scheme of the reports society / forest in Morocco. The population is especially of pastoral main activity in the bordering communes. But the oak groves of Mamora-Sehoul are integrated into the area of influence of several cities, what exposes the forest to the risks of uncontrolled urbanization. These oak groves are thus in the centre of interest of several stakeholders with opposite behaviour and a new paradigm of relation rural/urban. Through a double approach, environmental and socio-economic, this paper will try to bring elements of answer by analyzing the interactions between a forest which reached an alarming threshold of degradation and a society affected by important changes in its modes of intervention and exploitation.